A thinly veiled indirect discrimination: ECJ 14th March 2017 (C-157/15 & C-188/15) La velada discriminación indirecta (SSTJUE de 14 de marzo de 2017) - García Hernández, Joaquina (Anales de Derecho, 2017)
Abstract On 14th March 2017, the European Court of Justice made two decisions which solved some questions regarding the interpretation of different articles of the Directive 2000/78. These questions are related to religious discrimination in the workplace. Both employees were dismissed on account of their denial to do without the Islamic headscarf the activities which implied an interaction with customers. It is put foward, among other matters, which reasons can justufy a discriminatory behaviour by the employer and what consequences can produce for the company the worker showing of outward signs of religious beliefs within the contractual sphere. It is particularly analyzed the possible contractual default of the company with its customers. La velada discriminación indirecta -SSTJUE de 14 de marzo de 2017- El 14 de marzo de 2017 el TJUE dictó dos sentencias que dieron respuesta a cuestiones referidas a la interpretación de distintos preceptos de la Directiva 2000/78, relacionadas con la discriminación por motivos religiosos en el ámbito laboral. En ambos supuestos las trabajadoras demandantes se negaron a prescindir del velo islámico durante la realización de actividades que implicaran una relación personal con clientes, motivo por el que fueron despedidas. Se plantean, entre otras cuestiones, qué motivos son susceptibles de justificar una conducta discriminatoria por parte del empleador y qué consecuencias puede producir para la empresa la manifestación de las creencias religiosas del trabajador en el ámbito contractual, analizándose en concreto el eventual incumplimiento contractual de aquélla con sus clientes.